2002
DOI: 10.1007/s005340200014
|View full text |Cite
|
Sign up to set email alerts
|

Solitary necrotic nodule of the liver

Abstract: Solitary necrotic nodule of the liver is a rare benign lesion; only 22 cases have been reported to date. An unsolved problem in treating these lesions involves the difficulties in differential diagnosis; specific features of necrotic nodule of the liver in preoperative examinations have not been identified. Here, we report a patient with resected solitary necrotic nodule of the liver with preoperative features shown on ultrasound (US), computed tomography (CT), and magnetic resonance imaging (MRI) examinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 6 publications
2
22
0
Order By: Relevance
“…We postulate that these differences can be explained by different time points of observation in the evolution of solitary necrotic nodules. Early in their development, lesions show active inflammatory changes and angiogenesis that might be responsible for the high signal intensity on T2-weighted images [15] and the enhancement shown after contrast injection [13]. At a later stage, necrosis and devascularization can explain the different imaging appearances observed in our study [16].…”
Section: A C B Solitary Necrotic Nodules Of the Livermentioning
confidence: 38%
See 3 more Smart Citations
“…We postulate that these differences can be explained by different time points of observation in the evolution of solitary necrotic nodules. Early in their development, lesions show active inflammatory changes and angiogenesis that might be responsible for the high signal intensity on T2-weighted images [15] and the enhancement shown after contrast injection [13]. At a later stage, necrosis and devascularization can explain the different imaging appearances observed in our study [16].…”
Section: A C B Solitary Necrotic Nodules Of the Livermentioning
confidence: 38%
“…Previous authors have reported high signal intensity on T2-weighted images in two patients [14,15] and arterial enhancement with cross-sectional imaging [5,14,18] and angiography [13,20]. All of our cases showed low signal intensity on T2-weighted images and lack of enhancement.…”
Section: A C B Solitary Necrotic Nodules Of the Livermentioning
confidence: 66%
See 2 more Smart Citations
“…In the current study, no feeding arteries or history of parasitic infections were found. It was proposed that the SNN might have resulted from trauma or an immune response, followed by self-defense to form fibrous tissues surrounding the coagulation necrosis (16)(17)(18). Furthermore, a previous study showed foci of metastatic carcinoma in SNN that was associated with gastrointestinal cancer (5), and included four cases of ovarian tumors and five cases of gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 99%